Pattern of Problem Solving Skill Reviewed Based on Student Cognitive Style After Experienced Problem Based Learning Model with Ethnomathematics Nuances - Maulana, Ginanjar; Zaenuri, Zaenuri; Junaedi, Iwan (Universitas Negeri Semarang, 2020)
The 4Cs in 21st century skills consist of critical thinking, creativity, communication and collaboration. The skills are very importance in solving problem should be owned by students to face current century global advancement. This research aims to describe problem solving skill pattern of students based on cognitive style after being taught by Problem Based Learning (PBL) model with Ethnomathematics nuances. This mixed method research used sequential explanatory design. The qualitative research part was conducted first and then continued by quantitative research part. The qualitative research used technic and source triangulation. This study consisted of 23 subjects. They were selected based cognitive style test by using Matching Familiar Figure Test (MFFT) at fifth grade of Public Primary School Citimun I, Sumedang. Techniques of collecting data were observation, test, interview, and documentation. Reflective and Impulsive students could understand problems, design solution, and promote problem solving although they were incapable of accurately rechecking. Slow-Inaccurate students could understand problems but they were incapable to plan solution and solve problem. They also could not do rechecking accurately. It could be concluded that Reflective - Impulsive cognitive style typed students had more dominant in problem solving skill than Slow-Inaccurate cognitive typed students. Thus, PBL model with ethomathematics nuances can improve students' problem solving skills.